Posterior Quadratus Lumborum Block for Labor Analgesia: A Case Report. Issue 7 (May 2020) - de Haan, Johanna Blair; Tabba, Subhan; Lee, Linden O.; Ghebremichael, Semhar; Sen, Sudipta; Shoham, Daniel; Hernandez, Nadia
Abstract : Neuraxial analgesia has been established as the standard of care for labor analgesia. However, patients presenting with coagulopathy require anesthesiologists to explore alternate analgesic techniques. Systemic opioids may result in neonatal respiratory depression, and inhaled nitrous oxide may lead to nausea, vomiting, and over sedation and may not be readily available in all labor and delivery units. In this case report, we describe a case where posterior quadratus lumborum blocks provided effective analgesia in a parturient with Hemophilia A during the first stage of labor.